1998
DOI: 10.1021/bi972367v
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Heparin-Binding Properties of Human Clusterin

Abstract: Clusterin is a highly conserved mammalian glycoprotein which has been predicted to contain heparin-binding sites. We tested this prediction by studying the interactions between heparin and clusterin using ELISA and heparin affinity chromatography methodologies. Two forms of biotinylated heparin were used in ELISA: heparin which had been directly biotinylated with a biotin-N-hydroxysuccinimide ester and heparin which had been activated using epichlorohydrin and 1,6-diaminohexane prior to biotinylation. Both gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
4

Year Published

1999
1999
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 37 publications
4
22
0
4
Order By: Relevance
“…The binding affinities of both F1 P97 (0.27 Ϯ 0.02 M) and F2 P97 (1.89 Ϯ 0.33 M) for heparin are within the range reported for other heparin-binding proteins (0.3 nM to 4 M) such as antithrombin (2), interleukin-2 and -12 (14,24), clusterin (26), and the mycobacterial heparin-binding hemagglutinin (29), suggesting that these interactions are of physiological significance. The ability of the M. hyopneumoniae cilium adhesin to bind to components of the ECM, as well as to cilia, indicates that this molecule plays a multifunctional role in adherence to the porcine respiratory tract.…”
Section: Discussionsupporting
confidence: 78%
“…The binding affinities of both F1 P97 (0.27 Ϯ 0.02 M) and F2 P97 (1.89 Ϯ 0.33 M) for heparin are within the range reported for other heparin-binding proteins (0.3 nM to 4 M) such as antithrombin (2), interleukin-2 and -12 (14,24), clusterin (26), and the mycobacterial heparin-binding hemagglutinin (29), suggesting that these interactions are of physiological significance. The ability of the M. hyopneumoniae cilium adhesin to bind to components of the ECM, as well as to cilia, indicates that this molecule plays a multifunctional role in adherence to the porcine respiratory tract.…”
Section: Discussionsupporting
confidence: 78%
“…F3 P159 and F4 P159 were also shown to bind to heparin-agarose showing that these P159 recombinant fragments bind both soluble and bound heparin. These values are comparable to other biologically significant heparin-protein binding interactions (Pethe et al, 2000) and fall in the midrange of other reported constants for heparin-protein interactions (Pankhurst et al, 1998). The ability of F2 P159 to promote the adherence of latex beads to PK15 cells despite an inability to bind heparin suggests that different regions within P159 use different mechanisms to bind eukaryote cells.…”
Section: Discussionsupporting
confidence: 78%
“…Indeed AGEs stimulate vascular endothelial growth factor expression (35) and angiogenesis in vivo (36) and may play a role in choroidal neovascularization in AMD. A plausible drusen biogenesis scenario might first involve proteins like TIMP3, clusterin, and vitronectin, which normally interact with sulfated glycosaminoglycans (GAGs) (37)(38)(39), to noncovalently bind to the GAGs in Bruch's membrane. As oxidative stress defense mechanisms deteriorate with age, oxidative modifications may gradually lock these and other proteins to Bruch's membrane with crosslinks, preventing normal turnover and initiating drusen development.…”
Section: Discussionmentioning
confidence: 99%